OPTIMIZATION OF HIGH-SPEED MACHINING PARAMETERS OF THIN-WALLED ALUMINIUM STRUCTURES IN THE FUNCTION OF SURFACE ROUGHNESS - Vukman, Jovan; Milosevic, Mijodrag; Antic, Aco; Bozic, Dejan; Todic, Vladimir; Lukic, Dejan (Proceedings on engineering sciences (Online), 2024)
Due to their homogeneity and excellent ratio between load capacity and weight, thin-walled aluminum structures are used as structural parts in the aerospace, automotive and military industries. The manufacture of these thin-walled structures is mainly done by removing a large amount of material from full raw pieces, sometimes up to 95% of their initial mass. Because of a large volume of material removing, it is necessary to achieve high productivity, which is limited by the lack of rigidity of the thin walls of these structures. As a result, errors occur, while reducing accuracy and machining quality. The main subject and objective of this paper is related to the optimization of high-speed machining parameters of linear thin-walled structures made of aluminum alloy Al7075 from the aspect of surface quality of processed superficial as a goal function. For this purpose, experiments were carried out based on which conclusions were made of the influence of input parameters on the surface roughness.